Contributions of Selected Family Factors to Drug Abuse Among Adolescents in Secondary Schools in Manyatta Sub-county, Embu County, Kenya - Nyaga, Milcah Njoki; Mwai, Kimu (Science Publishing Group, 2016)
The aim of this research is to investigate the contributions of selected family factors to drug abuse among adolescents in Kenyan secondary schools. To achieve this, the study sought to investigate the role of parental monitoring, residence, employment and parenting behaviours in predisposing the adolescent in the development to drug use. In addition, the study established the significance of associations between family factors and drug abuse among adolescents. The data were collected from form two students and deputy principals in secondary schools. The findings revealed that lack of parental supervision, parental employment, authoritarian style of parenting and lack of open discussion with adolescents contributed to drug abuse as well as most parents do not take active roles in schools. The study further revealed that not residing with the biological parents was not significantly associatedwith drug abuse. This was contrary to the view held by most scholars that the adolescents who do not reside with their biological parents were prone to drug abuse. To avoid drug abuse, parental monitoring should be given to all children regardless of the birth order, absence of aggression at home, parental quality time, open discussions with adolescents, authoritative parenting and parental involvement in school activities. Majority of the children born after the first child portrayed antisocial behaviours; hence the further the birth position in the family the higher the engagement in drug abuse Based on these findings, there is need to give all children as much supervision as that given to the first born children. Thus, the schools should organise sessions for parents and educate them on effective ways of parenting adolescents. Parents need to be encouraged to take active role in schools. Therefore, schools must create partnerships by providing an open and accommodative environment with their wider community. This would help in forminga link between the school and the home as well as the school and the family.
doi: 10.11648/j.sjedu.20160402.11
Keywords: Adolescents; Drug Abuse; Students; Parents; Schools; Children